DEMOCRACY IN OUR HEMISPHERE AND THE ROLE OF THE ORGANIZATION OF AMERICAN STATES - Spehar, Elizabeth (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 1998)
The fiftieth anniversary of the American Declaration of the Rights and Duties of Man provides an appropriate opportunity to survey the state of democracy in our hemisphere and the role of the Organization of American States. Beginning in the mid 1980’s important progress in the establishment or restoration of democracy was made in a number of the Member States of the OAS, and the region today exhibits the majority of countries having completed the “transition” to democracy. At the same time many countries are still faced today with the challenge of the “consolidation” of democracy. The OAS has responded to this formidable challenge by adopting a collective and collaborative approach. Important amendments were made to the OAS Charter in order to implement the organization’s consensus regarding its obligation to preserve and uphold democracy in the region. Likewise, and as complements to the amendments, the OAS has also developed new mechanisms, such as the Unit for the Promotion of Democracy, policies such as the Inter-American Program to Combat Poverty and instruments like the Inter-American Convention Against Corruption, in order to contribute to the longer-term support of the consolidation of democracy. The continued viability of the Organization will depend on its ability to assimilate the changes occurring in the hemisphere as it evolves and to adapt its role to the emerging needs of the Member States, all while playing to its comparative advantage as the regional political forum of the Americas.